2019
DOI: 10.1136/bmjopen-2018-023491
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital delay and its associated psychosocial factors in patients presenting with acute appendicitis in a southwestern city in China: a single-centre prospective observational study

Abstract: ObjectivePrehospital delay is common among patients with acute appendicitis. The aim of this study was to measure the association of a wide range of psychosocial factors with the prehospital delay among adult patients with acute appendicitis in a southwestern city in China.MethodsSociodemographic, clinical, cognitive and psychosocial factors were collected from 421 adult patients with acute appendicitis from November 2016 to December 2017. In addition, factors associated with prehospital delay were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 55 publications
4
11
0
Order By: Relevance
“…This is the first qualitative investigation of prehospital patient behaviour in paediatric appendicitis and builds upon the knowledge gained by several projects investigating delay using patient surveys 8,17,28 . These methods simplified patient experience into quantitative data points created by a pre‐determined set of questions.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first qualitative investigation of prehospital patient behaviour in paediatric appendicitis and builds upon the knowledge gained by several projects investigating delay using patient surveys 8,17,28 . These methods simplified patient experience into quantitative data points created by a pre‐determined set of questions.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with research in other disease processes that have shown that lack of social support and low financial resources can cause delays in seeking care. (16,17) Patients who are socially disadvantaged with lower social support were less likely to undergo waitlisting and may require enhanced transplant navigation and support. Finally, the higher prevalence of Black/ African American patients among patients with elevated SIPAT scores may reflect higher rates of socioeconomic deprivation/chronic stress that culminates in higher psychosocial risk.…”
Section: Original Article | 661mentioning
confidence: 99%
“…Many research findings have found a correlation between the time interval and the risk of appendicitis perforation; a long wait before operation results in complicated appendicitis and, as a result, high postoperative morbidity [4][5][6][7]. Prehospital delay may have played a more significant role in the progression of appendicitis and future postoperative complications [3,5]. According to Li et al, delayed prehospital presentation for acute appendicitis was associated with older age, residing alone, lack of knowledge about the disease, low social support, negative characteristics of mental well-being such as introvert personality and poor coping style, low severity of the pain, and symptoms occurring during work hours [3].…”
Section: Introductionmentioning
confidence: 99%
“…During admissions, acute appendicitis is misdiagnosed in 3.8%-15% of all children cases and 5.95%-23.5% of all cases [ 2 ]. Its postoperative complication and morbidity rates remain high, about 29% and 18%, respectively [ 3 ]. Prehospital delay of acute appendicitis is defined as the time interval from when a patient with a history of acute appendicitis comes after at least 48 hours of symptom onset [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation